Conceptual Design of Unmanned Piston-Propeller Cargo Aircraft - F F H B Wiarso; B D Febriansyah; G A Gintings; R D Muhammad; H Muhammad (AVIA, 2021)
The need for a transportation system to transport goods is increasing, especially for regions in Indonesia that are included in the leading, remote, and disadvantaged (3T) categories. This paper will discuss the conceptual design of an unmanned cargo aircraft with a piston-propeller engine which can later be operated in the 3T area. The design will begin with a discussion of DRO, followed by a concept of the aircraft configuration. After the configuration is formed, the aerodynamic characteristics will be calculated, the weight will be predicted, and flight performance calculations and aircraft stability will be calculated